POTENSI TIGA VARIETAS TANAMAN SAWI SEBAGAI AKUMULATOR MERKURI PADA TANAH - Gema Junyo; Eko Handayanto (Jurnal Tanah dan Sumberdaya Lahan, 2017)
Mercury is one of heavy metals that is highly dangerous as it affects human health when it pollutes soils used for growing plants. The purpose of this study was to examine the potential of Brassica oleracea, Brassica rapa, and Brassica juncea in reducing levels of mercury in mercury-contaminated soil. Each of the three plant species was grown on a 3 kg of soil in a polybag which first contaminated with four concentrations of mercury (0 ppm, 0.5 ppm, 1 ppm, and 1.5 ppm ). The results showed that Brassica rapa accumulated mercury better then Brassica oleracea and Brassica juncea. On the soil contaminated with the lowest mercury concentration (0.5 ppm ), Brassica rapa root was able to absorb 0,081 ppm of mercury, at the concentration of 1 ppm, Brassica rapa root was able to absorb 0,091 ppm of mercury, while at the highest mercury concentration (1.5 ppm), Brassica rapa root was able to absorb 0,311 ppm. The ability of Brassica juncea roots to absorb mercury were better than those of Brassica rapa and Brassica oleracea.